Paternal presence and absence. Keys to understanding their emotional and formative implications. - Delabra Ríos, Bernardo Ángel (Emerging Trends in Education, 2023)
This is a book that, within the framework of studies on masculinities and paternities in our country, offers a perspective on a little explored dimension: the implications of the presence and absence of men, as fathers, in the life, daily life and relationships of the diversity of family arrangements that we can currently find. Both the theoretical elaboration that serves as an introduction to the book, as well as the particular studies that comprise it, offer a broad panorama of the ways in which, during the last few years, different social actors that make up family arrangements in our country live, experience, signify and re-signify the presence and absence of men as fathers. Absences due to issues as dissimilar as death, confinement, divorce and time absorbed by their jobs. Finally, these studies offer elements to rethink, theoretically, the emotional experiences and formative processes of people; formative in a broad sense, beyond the school as an institution, located in contexts of informal education, with all the complexity that this entails (Salguero & Yoseff, 2020).Translated with www.DeepL.com/Translator (free version)